การออกแบบแขนกลที่ทำงานด้วยความเร็วสูง - พลังรัฐ ธนการพาณิช (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The design and development of a high-speed 6-axis manipulator arm is carried on in this research. The detail study of inertia tensor for both Decoupled and Invariant are described as well as Inertia Ellipsoid. Before building the robot, the three different mechanisms are compared according to inertia matrices and power dissipations in the actuators when a force is exerted at the tip of the arm. Both inertia matrices and power dissipations are used as criteria for selecting the final robot configuration. Kinematics of the robot and Trajectory-following controllers are also described in details. The robot, that is developed for verifying result, consists of a five-bar-link mechanism to form a parallel drive mechanism for joint 2 and 3 while the rest joints are typical rotating. The experiments showed that at the maximum joint angular velocity, 240 deg/sec, the accuracy and repeatability are compatible to good conventional commercial robots.